Effects of process conditions on calorific value and yield of charcoal produced from pyrolysis of coconut shells - Ahmad, R.K. (Springer Science and Business Media Deutschland GmbH, 2020)
Charcoal, a black carbon residue, is mostly produced from the major conventional method where the biomass is allowed to be heated for several days in a kiln without studying the process condition. Most of the studies on the pyrolysis process focus on the liquid and gaseous by-products neglecting the solid to be used as a combustion fuel. For this study, charcoal was produced from coconut shells by the thermochemical conversion method of pyrolysis in a controlled nitrogen environment at temperatures of 300Â Â°C, 400Â Â°C, and 500Â Â°C, and residence times of 15Â min, 30Â min, and 60Â min. This was conducted to evaluate the process conditionsâ effects concerning the charcoal calorific value and yield. From the results obtained, a high process condition increases the calorific value, which results in a decrease in the charcoal yield. The lowest temperature gives a yield of 70.18Â wt and calorific value of 25.30Â MJ/kg while the highest temperature produces a yield for as low as 26.57Â wt and a high calorific value of 30.15Â MJ/kg. Furthermore, the charcoal yield tends to decrease from 51.99 to 33.10Â wt and the calorific value increases as the residence time increases from 15 to 45Â min. Consequently, the thermal conversion undergone by the biomass may cause the changes of the quality parameters. Thus, charcoal can replace the use of fossil fuels because it presents energy content higher than that of lignite and similar to that of coal. Â© Springer Nature Singapore Pte Ltd 2020.